Sölle and Mardelles: Glacial and periglacial phenomena in continental Europe - Troll, Carl (ERDKUNDE, 1962)
Most of the Norfolk hollow forms described by H. C. Prince in the preceding article correspond to the so-called Söllen (Sing. Soll) of the north-central European ground moraine landscapes. There is a more detailed older literature on them, summarized by W. Ropke (1929). From the possibilities of explanation two were still left in more recent times: the sinks as subglacial debris holes or as dead ice kettles. The explanation by dead ice melting had been varied by Ropke to the intramoraine ice melting theory. The dead ice theory is opposed by the fact that the one-walled dead ice forms occurring in stratified fluvioglacial deposits are mostly depressions of different size and irregular shape, often lobed, while the sinkholes are always small, circular or oval kettles. Just this can explain a new pingo theory. According to this theory, the tarns are the remains of periglacial ice-swelling mounds (Eskimo name Pingo), which after deglaciation leave a circular depression with a shallow ring wall surrounding it, i.e. thaw lakes in the sense of D. M. Hopkins. The proof of this origin has been led by Maarleveld and van den Toorn for a Soll in Dutch Friesland, i.e. in the old moraine landscape. For the mardells of the Paris Basin, the Hautes Fagnes, the Landes and Lorraine the new pingo theory has also been used. For the tarns of the young moraine landscapes in the surroundings of the Baltic Sea one had to assume with this explanation that after the retreat of the last ice age inland ice into the Baltic Sea basin still permanent freezing had formed.